Peran Product Innovation, Customer Experience Dan Perceived Value Dalam Repurchase Intention Pada Planet Surf Jepara - Amelia, Herta Rachma; Ali, Ali (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
This study aims to examine the role of Product Innovation, Customer Experience and Perceived Value in Repurchase Intention at Planet Surf in Jepara. The population of this study is buyers of Planet Surf products in Jepara. This study uses Quantitative research type. The data source in this study utilizes Primary Data. In this study, the survey stage was implemented through the stage of distributing questionnaires online via Google Form. The sampling technique used in the study was purposive sampling. The number of research samples obtained was 204 respondents. The statistical analysis method in this study was through the application of Partial Least Square (PLS) in SmartPLS Version 4.0. The findings of this study indicate that Product Innovation, Customer Experience and Perceived Value have a positive effect on Repurchase Intention.